Vanadium improves memory and spatial learning and protects the pyramidal cells of the hippocampus in juvenile hydrocephalic mice - Femi-Akinlosotu, Omowumi Moromoke; Olopade, Funmilayo Eniola; Obiako, Jane; Olopade, James Olukayode; Shokunbi, Matthew Temitayo (Frontiers in Neurology, 2023)
Background Hydrocephalus is a neurological condition known to cause learning and memory disabilities due to its damaging effect on the hippocampal neurons, especially pyramidal neurons. Vanadium at low doses has been observed to improve learning and memory abilities in neurological disorders but it is uncertain whether such protection will be provided in hydrocephalus. We investigated the morphology of hippocampal pyramidal neurons and neurobehavior in vanadium-treated and control juvenile hydrocephalic mice. Methods Hydrocephalus was induced by intra-cisternal injection of sterile-kaolin into juvenile mice which were then allocated into 4 groups of 10 pups each, with one group serving as an untreated hydrocephalic control while others were treated with 0.15, 0.3 and 3 mg/kg i.p of vanadium compound respectively, starting 7 days post-induction for 28 days. Non-hydrocephalic sham controls (n = 10) were sham operated without any treatment. Mice were weighed before dosing and sacrifice. Y-maze, Morris Water Maze and Novel Object Recognition tests were carried out before the sacrifice, the brains harvested, and processed for Cresyl Violet and immunohistochemistry for neurons (NeuN) and astrocytes (GFAP). The pyramidal neurons of the CA1 and CA3 regions of the hippocampus were assessed qualitatively and quantitatively. Data were analyzed using GraphPad prism 8. Results Escape latencies of vanadium-treated groups were significantly shorter (45.30 ± 26.30 s, 46.50 ± 26.35 s, 42.99 ± 18.44 s) than untreated group (62.06 ± 24.02 s) suggesting improvements in learning abilities. Time spent in the correct quadrant was significantly shorter in the untreated group (21.19 ± 4.15 s) compared to control (34.15 ± 9.44 s) and 3 mg/kg vanadium-treated group (34.35 ± 9.74 s). Recognition index and mean % alternation were lowest in untreated group (p = 0.0431, p=0.0158) suggesting memory impairments, with insignificant improvements in vanadium-treated groups. NeuN immuno-stained CA1 revealed loss of apical dendrites of the pyramidal cells in untreated hydrocephalus group relative to control and a gradual reversal attempt in the vanadium-treated groups. Astrocytic activation (GFAP stain) in the untreated hydrocephalus group were attenuated in the vanadium-treated groups under the GFAP stain. Pyknotic index in CA1 pyramidal layer of untreated (18.82 ± 2.59) and 0.15mg/kg vanadium-treated groups (18.14 ± 5.92) were significantly higher than control (11.11 ± 0.93; p = 0.0205, p = 0.0373) while there was no significant difference in CA3 pyknotic index across all groups. Conclusion Our results suggest that vanadium has a dose-dependent protective effect on the pyramidal cells of the hippocampus and on memory and spatial learning functions in juvenile hydrocephalic mice.